Heterogenous Subtypes of Late-Life Depression and Their Cognitive Patterns: A Latent Class Analysis - Wang, Li-Qi; Zhang, Tian-Hong; Dang, Wei; Liu, Sha; Fan, Zi-Li; Tu, Li-Hui; Zhang, Ming; Wang, Hua-Ning; Zhang, Nan; Ma, Qin-Ying; Zhang, Ying; Li, Hui-Zi; et al. (Frontiers in Psychiatry, 2022)
Background: Late-life depression (LLD), characterized by cognitive deficits, is considered heterogeneous across individuals. Previous studies have identified subtypes with diverse symptom profiles, but their cognitive patterns are unknown. This study aimed to investigate the subtypes of LLD and the cognitive profile of each group. Methods: In total, 109 depressed older adults were enrolled. We performed latent class analysis using Geriatric Depression Scale items as indicators to generate latent classes. We compared the sociodemographic and clinical characteristics with cognitive functions between groups and conducted regression analysis to investigate the association between class membership and variables with significant differences. Results: Two classes were identified: the “pessimistic” group was characterized by pessimistic thoughts and the “worried” group with a relatively high prevalence of worry symptoms. The two groups did not differ in sociodemographic characteristics. The “pessimistic” group showed a higher rate of past history of depression and lower age of onset. The “worried” group had more physical comorbidities and a higher rate of past history of anxiety. The “pessimistic” group was more impaired in general cognitive function, executive function, information processing speed, and attention. Lower general and executive functions were associated with the membership in the “pessimistic” group. Conclusions: Subjects with pessimistic symptoms and subjects with a propensity to worry may form two distinct subtypes of late-life depression with different cognitive profiles. Further, the cognitive evaluation of subjects with pessimistic symptoms is of utmost importance.